Long-term latitudinal effects of precipitation change in global monsoon regions - Ye, Wangting; Li, Yu; Feng, Zhuowen; Zhang, Yuxin; Peng, Simin (Frontiers in Earth Science, 2022)
Global paleomonsoon precipitation evolution is confined to asynchronous responses to global monsoons to shared forcings, including summer insolation, sea surface temperature, atmospheric circulation coupling, and ocean circulation. However, most studies are based on conclusions drawn from single or a few discrete records or deduced from top-down climate models, which limits our ability to understand the latitudinal effect of monsoon precipitation. In particular, precipitation is a locally constrained climate factor. Here, we present a comprehensive assessment of global monsoon precipitation over the last 12,000 cal year BP based on modern observations, paleoclimate simulations, paleoclimate records, and monsoon precipitation reconstructions over the past 12,000 cal year BP based on a bottom-up algorithm called climate field reconstruction approaches. The results show that the middle latitude monsoon precipitation is in line with the evolution of the insolation and significant long-term decreasing (increasing) trends in low latitude monsoon precipitation have not occurred over the last 12,000 years BP. For modern monsoon evolution, the monsoon precipitation also changes along the meridional direction, with overall decreasing precipitation in the global monsoon region and increasing precipitation in the monsoon margin area. Monsoon systems at different latitudes all record eight Holocene weak precipitation events, including the Younger Dryas (12,900 cal year BP to 11,700 cal year BP), which can be considered a strong effect caused by a significant reduction or collapse of a meridional ocean circulation system, namely, the Atlantic Meridional Overturning Circulation. Moreover, the low- and middle-latitude monsoon precipitation lags by approximately 2,000 years behind the onset of North Atlantic warming. Taken together, our findings provide important insights into the latitudinal effect of monsoon precipitation at different locations.